Lipoxin A4 selectively programs the profile of M2 tumor‐associated macrophages which favour control of tumor progression. Issue 2 (31st October 2016) - Simões, R. L.; De‐Brito, N. M.; Cunha‐Costa, H.; Morandi, V.; Fierro, I. M.; Roitt, I. M.; Barja‐Fidalgo, C.
Abstract : In tumor microenvironments, the macrophage population is heterogeneous, but some macrophages can acquire tumor‐promoting characteristics. These tumor‐associated macrophages (TAM) exhibit an M2‐like profile, with deficient production of NO and ROS, characteristics of pro‐inflammatory M1 cytotoxic macrophages. Lipoxins (LX) and 15‐epi‐lipoxins are lipid mediators which can induce certain features of M2 macrophages in mononuclear cells, but their effects on TAM remain to be elucidated. This study tested the hypothesis that ATL‐1, a synthetic analogue of 15‐epi‐lipoxin A4, could modulate TAM activity profile. We show that human macrophages (MΦ) differentiated into TAM‐like cells after incubation with conditioned medium from MV3, a human melanoma lineage cell. Contrasting with the effects observed in other M2 subsets and M1 profile macrophages, ATL‐1 selectively decreased M2 surface markers in TAM, suggesting unique behavior of this particular M2 subset. Importantly, these results were replicated by the natural lipoxins LXA4 and the aspirin induced 15‐epi‐LXA4 (ATL). In parallel, ATL‐1 stimulated TAM to produce NO by increasing the iNOS/arginase ratio and activated NADPH oxidase, triggering ROS production. These alterations in TAM profile induced by ATL‐1 led to loss of the anti‐apoptotic effects of TAM on melanoma cells and increased their cytotoxic properties. Finally, ATL‐1 was found to inhibit tumor progression in a murine model in vivo, which was accompanied by alterations in TAM profile and diminished angiogenesis. Together, the results show an unexpected effect of lipoxin, which induces in TAM a change from an M2‐ to an M1‐like profile, thereby triggering tumor cell apoptosis and down‐modulating the tumor progression. Abstract : What's new? Tumor‐associated macrophages (TAMs) can develop tumor‐promoting characteristics and suppress other immune cells. Lipoxins are lipid mediators that are known to affect macrophages, but their effect on TAMs is unclear. In this study, the authors found an unexpected effect of lipoxin, which induces in TAM a change from an M2‐ to an M1‐like profile, triggering tumor cell apoptosis and inhibiting tumor progression. These results reveal important differences in macrophage subsets associated with tumors, and suggest that lipoxins may provide a new therapeutic tool for cancer treatment.